Editorial Paper : Uniting Sensory Design, Computation, and Conservation: Integrated Trends in Contemporary Architecture - L.M.F Purwanto (JoDA Journal of Digital Architecture, 2026)
Editorial PaperUniting Sensory Design, Computation, and Conservation: Integrated Trends in Contemporary Architecture